Responses of the resident rocky crab (Halicarcinus planatus, Decapoda) to natural stressors and effluent discharges in Ushuaia Bay, Tierra del Fuego, Argentina - Diodato, Soledad Lorena (2012)
Ushuaia City has been growing since 1980 and industrial and domestic effluents have been discharged along its coasts. The present study evaluates the acute exposure of the rocky crab Halicarcinus planatus to three environmental stressors (salinity, pH and ammonia) and to in situ coastal whole effluents (Industrial Zone (IZ), Yacht Club (YC) and Encerrada Bay (EB)). Neither mortalities nor molting events were recorded during the study period. The highest physiological rates were at salinity 25, at pH 9.5 and at 3mg N-NH 3L -1 (174.38±17.76μg O 2h -1g -1 and 12.80±4.54μg N-NH 3h -1g -1; 199.45±11.86μg O 2h -1g -1 and 27.82±6.88μg N-NH 3h -1g -1; and 232±43.5μg O 2h -1g -1 and 26.29±3.42μg N-NH 3h -1g -1, respectively). Crabs exposed to the studied areas also showed a tendency to increase physiological parameters. Acetylcholynesterase (AChE) activity showed maximal inhibition in organisms from YC (0.14±0.07nmolmin -1mgprotein -1). H. planatus showed responses to both specific and complex environmental stressors and its use as a suitable bioindicator of environmental changes is discussed.